One-second coherence for a single electron spin coupled to a multi-qubit nuclear-spin environment - M. H. Abobeih (Nature Communications, 2018)
The coherence of quantum registers is limited by unwanted interactions, both between the qubits and with the environment. Here the authors extend the coherence time of a nitrogen-vacancy centre beyond a second by characterizing and decoupling its interactions with a multi-qubit nuclear spin environment.